PROPAGANDA MEDIA EROPA DALAM MENDUKUNG GENOSIDA ISRAEL DI PALESTINA 2024 - Wafi, Fadhlil; Maryolanda Zaini (The Journal of Society and Media, 2025)
Israel's genocidal actions today are increasingly massive in Palestine, which are supported by European media that have the same vision as Israeli Jews. This research aims to analyze how these European media support the Israeli genocide through propaganda disseminated in the form of news. To answer this research question, a descriptive qualitative approach is used to analyze the form of propaganda in European media. The findings of this study show that European media support the genocide by Israel through propaganda, such as deceiving facts about the Israeli genocide and the use of manipulative rhetoric to construct the diction of terrorism that is considered a Hamas group. From these two findings, it can be illustrated that European media not only spread news of conflict in the Middle East but also contributed to spreading propaganda to support genocide by Israel. This study's findings aim to further dialogue in communication science and media propaganda, serving as a reference for identifying and analyzing propaganda patterns used by countries.In other words, understanding the forms of media propaganda worldwide can minimize media bias or hidden agendas targeted at the international community.